Impact of the insurance costs on the competitiveness of food industry enterprises of Ukraine in the context of the food market security - Shirinyan, Lada; Arych, Mykhailo (My University, 2019)
The study was carried out to analyze insurance costs and to determine the trends, patterns and impact of the insurance costs on the competitiveness of food industry enterprises in the context of the food market security. The theoretical background of the article is based on critical literature review of the insurance costs, food market security and competitiveness. The research study was used the methods of comparative, statistical analysis of data, systematization, scientific interpretation; generalizations and comparisons the indicators of market share and capacity, profitability and efficiency, insurance costs and correlation-regression analysis methods and indicators. The hypothesis about the existence of a dependence between the competitiveness of FIEs and the portion of money allocated to FIEs for insurance is confirmed only for FIEs with high efficiency of doing business.
Keywords: кафедра фінансів; страхування; витрати; харчова промисловість; конкурентоспроможність; competitiveness; insurance; costs; security; food; конкурентоспособность; страхования; расходы; пищевая промышленность